Improved performance with fractional order control for asymmetrical cascaded H-bridge multilevel inverter - Vemula Anil Kumar; Arounassalame Mouttou (Institute of Advanced Engineering and Science, 2020)
This paper proposes a control scheme for seven level asymmetrical cascaded H-bridge multi level inverter (ACHBMLI) based on fractional order calculus. The seven level ACHBMLI consists of two H-bridges that are connected in series and are excited by different dc voltage sources. A simplified model is developed by assuming the small signal variation component is equal in both the H-bridges. A fractional order PID (FO-PID) controller is designed for the ACHBMLI using the simplified model. Simulation study shows the adequacy of FO-PID controller in giving an output voltage with minimum distortions. A conventional PID controller is also designed for ACHBMLI using the same simplified model. The performance of the ACHBMLI with FO-PID controller is compared with the performance of ACHBMLI with conventional PID controller. The simulation results prove the superiority of FO-PID controller in maintaining the output voltage of the ACHBMLI close to the reference voltage and in reducing the harmonic distortion of output voltage of the inverter. The simulation was done using MATLAB and the parameters of FO-PID controller was designed using FOMCON tool box.